Adapting first aid education to fragile contexts: A qualitative study (International Journal of First Aid Education)
Evidence for international first aid guidelines predominantly comes from studies conducted in western contexts during peacetime and/or healthcare settings. Yet, internationally the burden of trauma falls on low- and middle-income countries where lay responders might have to act in fragile contexts, where first aid and healthcare resources are limited or not available. This study focuses on the principles and practices that govern first aid education (FAE), versus clinical evidence of first aid interventions. Accepting that application of first aid may vary according to context, we sought to understand educational principles according to contextual resources of fragile and non-fragile environments. We interviewed educators, from six countries where conflict, geography or resources deemed them to be fragile, to explore which educational approaches were used and found effective in educating potential lay responders. Through qualitative analysis, we identified educational approaches and themes including: